Non‐Heme‐Iron‐Mediated Selective Halogenation of Unactivated Carbon−Hydrogen Bonds. Issue 4 (7th December 2021) - Bleher, Katharina; Comba, Peter; Faltermeier, Dieter; Gupta, Ashutosh; Kerscher, Marion; Krieg, Saskia; Martin, Bodo; Velmurugan, Gunasekaran; Yang, Shuyi
Abstract: Oxidation of the iron(II) precursor [(L 1 )Fe II Cl2 ], where L 1 is a tetradentate bispidine, with soluble iodosylbenzene ( s PhIO) leads to the extremely reactive ferryl oxidant [(L 1 )(Cl)Fe IV =O] + with a cis disposition of the chlorido and oxido coligands, as observed in non‐heme halogenase enzymes. Experimental data indicate that, with cyclohexane as substrate, there is selective formation of chlorocyclohexane, the halogenation being initiated by C−H abstraction and the result of a rebound of the ensuing radical to an iron‐bound Cl − . The time‐resolved formation of the halogenation product indicates that this primarily results from s PhIO oxidation of an initially formed oxido‐bridged diiron(III) resting state. The high yield of up to >70 % (stoichiometric reaction) as well as the differing reactivities of free Fe 2+ and Fe 3+ in comparison with [(L 1 )Fe II Cl2 ] indicate a high complex stability of the bispidine‐iron complexes. DFT analysis shows that, due to a large driving force and small triplet‐quintet gap, [(L 1 )(Cl)Fe IV =O] + is the most reactive small‐molecule halogenase model, that the Fe III /radical rebound intermediate has a relatively long lifetime (as supported by experimentally observed cage escape), and that this intermediate has, as observed experimentally, a lower energy barrier to the halogenation than the hydroxylation product; this is shown to primarily be due to steric effects. Abstract : Slowly, but surely : The iron(IV)‐oxido complex [(L 1 )(Cl)Fe IV =O] + with a chloride in cis position to the oxido group is an excellent model for non‐heme‐iron halogenases: it activates the very strong C−H bonds of cyclohexane and selectively leads to the halogenated product. Although it is the fastest iron(IV)‐oxido model system known, formation of an oxido‐bridged diiron(III) resting is the dominating reaction, and the halogenation itself therefore is a relatively slow but still selective process.